Integrating Smart City Technologies to Enhance Police Performance and Urban Public Safety - Cucuk Kristiono (Universitas Negeri Semarang, 2025)
The rapid growth of smart cities offers new opportunities for enhancing policing efficiency, urban safety, and public trust. This study investigates the integration of smart city technologies—such as IoT-based surveillance, real-time data platforms, intelligent traffic systems, and predictive analytics—into modern law-enforcement operations. Using a mixed-methods approach, the research analyzes operational data from three metropolitan smart city projects, along with 58 interviews involving police officers, urban planners, technology developers, and community representatives. Quantitative findings demonstrate that smart city integration reduces emergency response times by 24%, improves crime detection rates by 31%, and enhances traffic incident management by 42% through automated sensors and connected infrastructure. Qualitative results reveal that police officers benefit from improved situational awareness, yet express concerns about data overload, privacy implications, and insufficient interoperability among digital systems. The study concludes that smart city technologies significantly strengthen public safety when supported by robust governance, ethical data management, and inter-agency collaboration. This research contributes to urban safety science by offering a comprehensive framework for aligning policing functions with smart city infrastructures to achieve sustainable and citizen-centered outcomes.